2006
DOI: 10.1038/sj.ejcn.1602552
|View full text |Cite
|
Sign up to set email alerts
|

Higher maternal dietary protein intake in late pregnancy is associated with a lower infant ponderal index at birth

Abstract: Aim: A high ponderal index at birth has been associated with later obesity and it has been suggested that intervention to prevent obesity and its sequela should consider the antenatal period. In this context, we investigated the association between maternal nutrition and birth anthropometry. Design: We analyzed data on 1040 mother-infant pairs collected during the Tasmanian Infant Health Survey (TIHS), Tasmania, 1988Tasmania, -1989. Maternal dietary intake during pregnancy was measured by food frequency que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
47
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 69 publications
6
47
4
Order By: Relevance
“…A positive association with birthweight was found for %TE from carbohydrate in early pregnancy (Cohen et al, 2001), monounsaturated fat intake in late pregnancy (Petridou et al, 1998), protein intake in early pregnancy (Doyle et al, 1990;Cuco et al, 2006), %TE from protein in early pregnancy (Moore et al, 2004) and protein intake in late pregnancy (Haste et al, 1991;Cuco et al, 2006). Other studies have found birthweight declines with high protein intakes (Andreasyan et al, 2007). These varying results are not inconsistent considering the close correlation of these macronutrients and the quadratic relationship between carbohydrate, protein and fat intakes and birthweight found in our study.…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…A positive association with birthweight was found for %TE from carbohydrate in early pregnancy (Cohen et al, 2001), monounsaturated fat intake in late pregnancy (Petridou et al, 1998), protein intake in early pregnancy (Doyle et al, 1990;Cuco et al, 2006), %TE from protein in early pregnancy (Moore et al, 2004) and protein intake in late pregnancy (Haste et al, 1991;Cuco et al, 2006). Other studies have found birthweight declines with high protein intakes (Andreasyan et al, 2007). These varying results are not inconsistent considering the close correlation of these macronutrients and the quadratic relationship between carbohydrate, protein and fat intakes and birthweight found in our study.…”
Section: Discussioncontrasting
confidence: 39%
“…Petridou et al (1998) found higher meat and fish intakes were suggestively associated, and MUFA intake significantly associated with increased birthweight. Mitchell et al (2004) found that intake of iron supplements in late pregnancy was associated with increased birthweight whereas Andreasyan et al (2007) found increasing protein intake was negatively associated with birthweight.…”
Section: Introductionmentioning
confidence: 93%
“…A recent article showed that a 30% reduction in total energy intake resulted in structural abnormalities of the brain without any change in brain mass (30). On the other hand, a 10-g/d increase in protein intake led to an 18-g reduction in birth weight without any observed change in head circumference (31). While clearly observational studies such as ours cannot test the effect of protein intake on brain development, they do support a need for further investigations, initially through animal studies.…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional factors associated with poor placental growth include increased maternal carbohydrate intake in early and late pregnancy and decreased maternal protein intake in late pregnancy (16,17).…”
Section: Introductionmentioning
confidence: 99%